Knowledge mapping of supply chain risk research based on CiteSpace. (4th March 2020) - Sun, Ling; Xu, Xu; Yang, Yanbin; Liu, Wei; Jin, Jiahao
Abstract: Supply chain risk is a relatively new research field, and research results have been published in journals, and in master and doctoral articles. In this article, we first performed a quantitative analysis of existing literature on supply chain risk indexed in Web of Science (WOS). Then, we analyzed the author, institution, keywords, research hotspot, and cocited literature of existing publications in the research field of supply chain risk by using CiteSpace. The aim of this study is to investigate the trend, geographical distribution, author distribution, research field, keywords, keyword clustering, and other features of scientific articles on supply chain risk published in global journals, using the most advanced bibliometric analysis tools. The results of this study can be used to determine the most influential research institutions and authors in the research field of supply chain risk, as well as the research hotspots in different periods, and different research directions in this field.